HASIL BELAJAR FISIKA SISWA MELALUI PENERAPAN PEMBELAJARAN KREATIF MODEL INSTRUKSIONAL DDFK PROBLEM SOLVING DENGAN TEKNIK NOMINAL GROUP DI KELAS XI IPA1 MAN 2 MODEL PEKANBARU - M. Rahmad; Sugiono Sugiono; Zulhelmi Zulhelmi (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2009)
This study aims to describe the cognitive learning outcomes of students in learning physics throughthe application DDFK Problem Solving with the nominal group technique in MAN 2 ModelPekanbaru in the school year 2008/2009 on the subject matter of static fluid. Subjects studied areclass XI student IPA1 totaling 33 students. Data collection instrument is a test of cognitive learningoutcomes. Data collection techniques is a technique that in tests done after the learning process.The data, analyzed by descriptive analysis. From the analysis of data obtained by the averageabsorption was 79.0 % with good categories and effectiveness of learning with the category quiteeffective. Student learning exhaustiveness 61% and 73% of learning objectives with incompletecategory. Based on the results of data analysis can be concluded that through the implementationDDFK Problem Solving with the nominal group technique gives the average results of learningboth in class XI IPA1 MAN 2 Model Pekanbaru on the subject matter of static fluid.